Desentralisasi program Keluarga Berencana: Tantangan dan persoalan kasus Provinsi Kalimantan Barat - Purwaningsih, Sri Sunarti (Jurnal Kependudukan Indonesia, 2012)
One of the main objectives of regional autonomy is to improve the access and quality of services given by the government. However, the implementation of it actually faces several problems, and that includes the family planning sector. This paper is intended to raise a discussion related to the challenges and issues that were faced while implementing the decentralization of the family planning sector in the national level, and in specific the West Kalimantan Province’s case. On the national level, the challenges that are encountered, among other things, are: The changes in the authority and organizational structure of the family planning; budget reductions and human resources; and the declining of the population performance indicator. When it comes to the West Kalimantan Province’s case, the challenges in managing the family planning program were in consequence of, among other things, the decrease of the PLKB’s number, and the ability of the local governments budget to providing contraceptives. This was especially so after the implementation of regional autonomy. After the decentralization of the family planning program, in general the local governments’ (regency/city) commitment has deflated compared to the era when decentralization was not yet implemented. In order to address these problems, the revitalization of the family planning program has been initiated by the central government. F amity planning needs to be re-emboldened, equipped with right synergy between the local governments (provincial and regional) and the central government.